CAR T-cell therapies for T-cell malignancies: does cellular immunotherapy represent the best chance of cure? - Nicola Maciocia; Brandon Wade; Paul Maciocia (Blood Advances)
Abstract: Chimeric antigen receptor T-cell (CAR-T) therapy has proven successful for B-cell lymphomas and leukemias. This success has inspired the development of CAR-T for T-cell malignancies. T-cell lymphomas and T-cell acute lymphoblastic leukemia (T-ALL) are highly heterogenous diseases but are united by poor prognosis in the relapsed/refractory setting and the lack of any novel, targeted therapies. CAR-T therapy is a promising solution for these diseases but carries a number of challenges, principally that target antigens are typically shared between malignant and normal T cells. This can cause issues with fratricide and T-cell aplasia. In this review we discuss the current state of CAR-T treatment for T-ALL and T-cell lymphomas, highlighting recent novel clinical data for T-cell malignancies and discuss lessons that can be learned for future research in this area.